2004
DOI: 10.1136/sti.2003.006239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of real time polymerase chain reaction assays for confirmation of Neisseria gonorrhoeae in clinical samples tested positive in the Roche Cobas Amplicor assay

Abstract: Objective: Development of a rapid, sensitive, and accurate assay for confirmation of Neisseria gonorrhoeae in clinical samples. Method: Two real time polymerase chain reaction (PCR) assays, developed on the LightCycler for amplification of the N gonorrhoeae cppB gene, were utilised for confirmation of this bacterial pathogen in samples positive by the Roche Cobas Amplicor assay. Performance characteristics of the two assays were compared with other commercial nucleic acid amplification assays, including the Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 16 publications
1
38
0
1
Order By: Relevance
“…En cuanto a la infección por N. gonorrhoeae, solo se encontró un caso en una mujer asintomática, hallazgo que coincide con otros reportes que demuestran una alta proporción de casos asintomáticos de esta infección en las mujeres (12). La ausencia de infección concomitante difiere de lo hallado en otros estudios en los Estados Unidos, en los que se ha encontrado que ésta se presenta hasta en 50 % de las mujeres de 15 a 19 años que consultan en los servicios de salud (14); sin embargo, en otras poblaciones del mismo país se ha informado una proporción más baja de infección concomitante, como es el caso de un grupo de adolescentes asistentes a colegios de Nueva York, en el que la proporción fue de 3,5 % (35).…”
Section: Resultsunclassified
“…En cuanto a la infección por N. gonorrhoeae, solo se encontró un caso en una mujer asintomática, hallazgo que coincide con otros reportes que demuestran una alta proporción de casos asintomáticos de esta infección en las mujeres (12). La ausencia de infección concomitante difiere de lo hallado en otros estudios en los Estados Unidos, en los que se ha encontrado que ésta se presenta hasta en 50 % de las mujeres de 15 a 19 años que consultan en los servicios de salud (14); sin embargo, en otras poblaciones del mismo país se ha informado una proporción más baja de infección concomitante, como es el caso de un grupo de adolescentes asistentes a colegios de Nueva York, en el que la proporción fue de 3,5 % (35).…”
Section: Resultsunclassified
“…Recently, two independent studies investigated the use of N. gonorrhoeae cppB PCR assays on populations in Australia and the Netherlands. 50, 51 Tabrizi et al 51 found no false-negative results and considered the cppB gene assay to be suitable for use in a population in Victoria, Australia, whereas Bruisten et al 50 found a high incidence (5.8%) of false-negative results and concluded that the cppB gene target was not suitable for use in the Dutch population. Interestingly, other Australian studies have revealed a high incidence of cppB-related false-negative PCR results in a patient population in the Northern Territory in Australia, due to the recent appearance and expansion of a non-PAU Ϫ gonococcal subtype.…”
Section: Sequence-related Challenges For Gonorrhea Naat Assaysmentioning
confidence: 99%
“…57,72 Supplementary tests for the Roche Amplicor assay have included a 16S PCR assay provided by Roche as well as various in-house PCR methods targeting the cppB gene. 51,64,90 Roche later withdrew the 16S assay from the marketplace, so cppB gene-based PCR assays were widely adopted for confirmation. However, cppB gene-based NAAT assays are now no longer considered adequate for some patient populations because of the limitations outlined previously.…”
Section: Roche Cobas Amplicormentioning
confidence: 99%
“…An additional PCR for amplification of ␤-globin sequence was conducted for detection of inhibition and sample adequacy (22).…”
Section: Methodsmentioning
confidence: 99%